Methanol adsorption on magnesium oxide surface with defects: A DFT study - Branda, Maria Marta (2003)
The methanol adsorption on several defects of the magnesium oxide surface were studied. Structural and electronic study with geometrical optimization and natural bond orbital (NBO) analysis were performed using a density functional theory (DFT) method. Oxygen and magnesium with different coordination numbers have very different reactivity in this surface producing dissociated and non-dissociated species. These results are in agreement with infrared spectroscopy observations where CH3OH, OCH3 and OH species were found in defective MgO surfaces.